A figura paterna na família: Uma análise a partir da abordagem de Deuteronômio 6.4-9 - Wehrmann Reinar, Haidi (Vox Scripturae - Revista Teológica Internacional, 2010)
This article is about a bibliographic research on the father figure in the family. We have analyzed if there are a truly absence of the father in the family, the reasons of that, and the consequences for the children. In the second part, we have exegeticaly analyzed the text of Deuteronomy 6.4-9, where there is the commandment to love God beyond all other things, and a teaching about teaching the children to love and obey God, it means that the religious teach starts at home with the parents. But, to make it real, the father should be present in the life of his family and children, because the education of the children it is not responsibility of the mother alone. In the third part, we have analyzed the actual reality, where the majority of cases do not allow a deeper relationship with the father, and much times even with the mother. We want to highlight the importance of the text we analyzed to our time, and we want to learn some guidelines of the religious education. Therefore we have appointed some propositions that make possible to father to become more present in the life and education of his children.
Keywords: father; family; Deuteronomy; religious education at home; to love God